The cultural significance of modern human morphology - Kruse, Andy, author; Glantz, Mica, advisor; Van Buren, Mary, committee member; LaBelle, Jason, committee member; Fiege, Mark, committee member (Colorado State University. Libraries, 2012)
The dominant opinion in paleoanthropology maintains that 'modern' behavior resulted from innovations made by anatomically modern humans without the development of this behavior in archaic hominin groups. To a large degree, the archaeological record supports this dogma since much of the evidence for 'modern' behavior is found associated with anatomically modern human fossils. However, other evidence is surfacing that suggests 'modern' behaviors to be associated with other hominin groups independently of modern humans. Through a comparative analysis of 15 Pleistocene Neanderthal and modern human sites from Africa, the Levant, and Eurasia, I test this longstanding assumption. While my results reveal that anatomically modern humans do in fact appear to be the dominant producers of 'modern' behavior, evidence for this behavior is also conclusively present in Neanderthals. Therefore we can declare that 'modern' behavior does not match modern morphology in the archaeological record and thus reject the dogma that anatomically modern humans were the sole producers of 'modern' behavior. Additionally I find that the evolution of these behaviors was not a straightforward progression, but a mosaic of developments that varied across region, period, and species.
Keywords: behavior; homo sapiens; human; modern; neanderthals; paleoanthropology